Multiprofessional geriatric outpatient service: a perspective of health care for the elderly in interdisciplinary approach - Remor, Camila Bitencourt (2012)
Many scientific publications stress the importance of the interdisciplinary approach in the healthcare for the elderly. However, few reports have described successful experiences on healthcare for the elderly patient from a multi-professional group. Therefore, this article describes the experience of a team of multi-professional residents in constructing an outpatient health care of the elderly towards an interdisciplinary approach. The team was composed for nurses, nutritionists, physical-therapists, psychologist, social-worker, pharmacist, accompanied by a field preceptor, tutors core and geriatricians. The flow of the ambulatory care unit and started with the referral of elderly patients in a geriatric outpatient clinic, from medical appointments as needed health care for the elderly for three or more professionals in the multidisciplinary team. The attendances were directed from multidisciplinary evaluations. It was observed that the awareness of professionals about the need to invest in interdisciplinary actions was crucial in the implementation of the clinic. The performance teamwork led to the development of a holistic view of the elderly, in order to plan a comprehensive care and, behold much of their multiple health needs.